A Review on Gamification in e-learning: Effects and Challenges - Senthil kumaran V; Nithiya Shri M; Harini A (Jurnal Pendidikan, 2023)
Information technology has brought us a great deal of technological advancement, opening up endless possibilities for distance education. E-Learning platforms make it possible to connect people around the globe. Using the various technologies that are available, Gamification enhances the performance of e-learning platforms. Gamification of e-learning platforms helps in providing an engaging learning experience for users of all ages. Applying gamification in a non-gaming environment motivates students and also keeps them engaged in learning. This paper summarizes various game elements such as points, leader boards, badges, provided to the users for better e-learning experience by gamifying the environment and discussing the impact of gamification.